2019
DOI: 10.12746/swrccc.v7i31.595
|View full text |Cite
|
Sign up to set email alerts
|

Critical illness-related corticosteroid insufficiency: What we know and what we don’t know

Abstract: Glucocorticoids have an important role in the maintenance of vascular tone, endothelial integrity, and vascular permeability in the setting of acute illness. 1 Elevation of plasma cortisol concentrations is part of the adaptive mechanisms in acute illness and inappropriately low plasma cortisol has been linked with increased mortality. 2,3 Based on this, the concept of critical illness-related corticosteroid insufficiency (CIRCI) was first introduced in 2008 4 and refers to inadequate cellular corticosteroid a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Binary logistic regression analysis revealed that physicians in the southern and western regions were statistically less likely to possess knowledge of CIRCI compared to their counterparts in the central region. This lack of knowledge among physicians may be attributed to the absence of precise diagnostic criteria for identifying patients who do not exhibit an elevation in cortisol levels during acute illness [ 9 ]. It is important to note that the level of total cortisol does not accurately reflect steroid levels, as it is influenced by free cortisol and its interaction with cortisol receptors.…”
Section: Discussionmentioning
confidence: 99%
“…Binary logistic regression analysis revealed that physicians in the southern and western regions were statistically less likely to possess knowledge of CIRCI compared to their counterparts in the central region. This lack of knowledge among physicians may be attributed to the absence of precise diagnostic criteria for identifying patients who do not exhibit an elevation in cortisol levels during acute illness [ 9 ]. It is important to note that the level of total cortisol does not accurately reflect steroid levels, as it is influenced by free cortisol and its interaction with cortisol receptors.…”
Section: Discussionmentioning
confidence: 99%
“…Patients afflicted with CIRCI usually present with refractory hypotension which may also be accompanied by hypoglycemia, electrolyte abnormalities, metabolic acidosis, and eosinophilia. 7 The incidence of CIRCI can be as high as 60% in patients with septic shock. 8 Analysis of different cohorts shows that the incidence of CIRCI among patients with sepsis ranged from 12% to as high as 75%.…”
Section: Introductionmentioning
confidence: 99%
“…Critical illness-related corticosteroid insufficiency or CIRCI, which refers to an inadequate and blunted corticosteroid response to the level of stress, is an underrecognized condition in the critical care arena. 1 It occurs in about 30-70% of critically ill patients 2 and can be as high as 77% in patients with sepsis. 3 The clinical presentation of CIRCI is ominous, commonly manifesting with shock refractory to fluid resuscitation and vasopressors.…”
Section: Introductionmentioning
confidence: 99%